Post Reconstitution Stability of Co-Amoxiclav Injection for Multiple Usages in Developing Countries - Mazlina M Said (Journal of Global Pharma Technology, 2020)
OBJECTIVE: Co-amoxiclav injections are stored after reconstitution by healthcare givers for multiple usage contrary to manufacturer’s instructions in pediatric patients to reduce the cost of treatment in developing countries. The purpose of this study is to determine the percentage content of amoxicillin and clavulanic acid in co-amoxiclav injections at the point of administering of second dose after reconstitution.METHODS: Samples were reconstituted according to manufacturers’ instructions and stored in a refrigerator (2-5°C) and at tropical temperature (30°C and 75% RH). The samples were assayed immediately and then 8 hours after reconstitution. The assay was carried out using HPLC according to the USP monograph for amoxicillin-clavulanic acid suspension and the percentage content during the administration of the second dose was calculated in reference to a freshly prepared samples.RESULTS: The percentage content of amoxicillin and clavulanic acid in refrigerated samples was <70% and <35% of the freshly prepared samples respectively, While at simulated tropical room temperature, it was <45% and <15% of the freshly prepared samples respectively.CONCLUSION: The study showed that storage of reconstituted co-amoxiclav injection will lead to administering of lower dose at the point of admistration of the second dose; this will lead to treatment and antibiotic resistance.